THE INFLUENCE OF K3, WORKLOAD AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION - Nono Dwi Arifiyanto; Kuswandi Kuswandi; Sri Rahayu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to examine the influence of K3, workload and work environment on employee performance through job satisfaction. This research is a quantitative research using a saturated sample of all employees at PT Varia Usaha Beton Gempol Pasuruan Area, East Java, Indonesia are 69 people. The results of the questionnaire distributed via Google Form were processed using the SPSS 25.0 program. The research results are as follows: K3 has a significant effect on job satisfaction and employee performance, Workload and work environment have no significant effect on job satisfaction and employee performance, Job satisfaction has a significant effect on employee performance, but job satisfaction does not mediate K3, workload and work environment on employee performance. This research aims to fill the gap by examining the relationship between K3, workload, work environment, job satisfaction and employee performance. Thus, it is hoped that this research can provide a more comprehensive understanding of the factors that influence employee performance at PT Varia Usaha Beton and provide a significant contribution to the development of knowledge in the field of human resource management.